Correlation between red and blue magnitude of stars in open cluster M34 / Nor Azida Abdul Aziz - Abdul Aziz, Nor Azida (2007)
An open cluster is a group of up to a few thousand stars that were formed the same giant molecular cloud, and is still gravitationally bound to each other. They are believed to originate from large cosmic gas and dust clouds in the plane of Milky Way. To determine the instrumental magnitude of the stars in this research, the aperture photometry method were used. The aperture photometry is a method of CCD photometry for determining the star's brightness with the use of three digital annulus to measure the brightness of the star. The scale used to represent the star's brightness is magnitude. In this research, 14 inch Celestron Telescope and CCD Camera Model ST-8XME were used. This research is done with the objective of to measure the correlation between blue and red magnitude of stars in open cluster M34, to know how to align a telescope and grab image using Charge Coupled device (CCD) camera and to know how to use Astronomical Image Processing (AIP) software to calculate the instrumental magnitude of stars. M34 is the open cluster used in this research. The instrumental magnitude of stars using blue filter are smaller than the instrumental magnitude of stars using red filter. From the value of the magnitude of the stars, the image of the stars using blue filter is brighter compare to the image using red filter. This show that blue filter has higher intensity and smaller wavelength than red filter for M34. For signal to noise ratio, blue filter has a higher value compare to red filter. From this value, it confirms that blue intensity is higher than red.